PENGARUH VICARIOUS LEARNING TUI NA MASSAGE TERHADAP KENAIKAN BERAT BADAN ANAK USIA 12-47 BULAN - Wuna, Wa Ode Sri Kamba; Andriyani, Andriyani (Media Penelitian dan Pengembangan Kesehatan, 2023)
The nutrition issue is closely related to meeting the nutritional needs of toddlers. Toddlers aged one to three years are in the 'food jag' stage, where they often eat only foods they like and may have difficulty eating. The eating difficulties in toddlers can be addressed through non-pharmacological methods such as massage. Toddler massage is a tactile stimulation technique that can stimulate muscles, bones, and organ systems to function optimally, increase the body's metabolism, and, consequently, promote weight gain in infants. Tui Na Massage is a massage technique that can improve blood circulation in the spleen and digestive system through acupressure modification, specifically designed to address feeding difficulties in toddlers. One strategy to enhance Tui Na Massage's practice is through video-based learning. This study aimed to examine the influence of Vicarious Learning Tui Na Massage through video media on the weight gain of children aged 12-47 months. The research method used is a quasi-experimental design with a control group. The sample in this study consists of toddlers in the Poasia Community Health Center area, selected using purposive sampling, totaling 32 toddlers, with 16 in the control group and 16 in the intervention group. The result showed the Paired T-Test yielded a p-value of <0.05, indicating that Vicarious Learning Tui Na Massage has an impact on the weight gain of children aged 12-47 months. It is recommended that the Tui Na Massage video be promoted to parents as a non-pharmacological approach to improving children's weight.